Receivable and Profitability: Analysis of Nigeria Manufacturing Companies with Random Effect - Adegbite, Tajudeen Adejare (Master of Management, Faculty of Economics and Business, Diponegoro University, 2024)
ABSTRACTThis study examined the effect of receivable on profitability in Nigeria manufacturing companies. Panel data analysis components such as random, and fixed effects as well as pooled regression were employed to analyse the data collected from annual reports of selected manufacturing companies in Nigeria. Based on the finding for the reliable analytical tools, it was discovered that Days Sales Outstanding (DSO) increased Profitability significantly. Also credit policy increases profitability positively and significantly indicating that there is a positive effect of credit policy on Profitability. Conversely, other variables which are the control variables such as industry types, economic environment, and company size had negative effect on profitability. Conclusively, receivable has positive impact on profitability in Nigeria manufacturing industries. It is recommended that companies should inversely reduce Days Sales Outstanding periods foe the collection of debts owned by their consumers for effective production utilization so as to ultimately upsurge Nigeria companies’ profitability significantly and tremendously. Also, the credit policy of the companies should be reviewed to be friendlier for the customers so that accommodate more customers for effective increment in patronage and profitability.